6ER-022 The development and clinical application of tpn control software led by pharmacists in cancer hospital. (2nd March 2018) - Wang, Z; Shao, Y; Yang, G; Zhao, Q; Shi, L; Zhou, C; Peng, Y; Huang, P
Abstract : Background: The reasonable ratio of total parenteral nutrition after tumour surgery is beneficial in the recovery of postoperative patients. However, in clinical practice, the normative application of nutritional support does not catch clinical attention. Purpose: To introduce the development of total parenteral nutrition (TPN) control software which is led by pharmacists in a cancer-specialised hospital, and evaluate the effect of the application of TPN control software on the standardisation of TPN orders in patients with colorectal cancer after surgery. Material and methods: Based on the hospital information system (HIS), pharmacists and information technology professionals joint-developed a suitable TPN control software which could manage the range of the total heat, glycolipid ratio, the ratio of heat to nitrogen, electrolytes and other indexes. The system was applied in the Surgical Department of Abdominal Oncology on 1 July 2015, and the TPN prescription standardisation effect of the system was evaluated by comparing the information on colorectal cancer patients treated 3 months after the application of the system to the control participants treated 3 months' before. Results: A total of 387 TPN prescription-treated patients with colorectal cancer, who underwent surgery, were analysed. The cohort comprised 200 participants, who received the treatment 3 months before the application of theTPN prescription system and 187 participants, who received the treatment 3 months' after. The sex, age, performance status (PS) score and body mass index (BMI) of the two groups did not differ significantly (p>0.05). The rates of optimised TPN prescriptions after implementation of the TPN control system increased significantly (p<0.01). In detail, the standard rate of glycolipid ratio and heat to nitrogen respectively accounted for 66% (132) and 59.5% (119), after application of the system, both increased to 97.86% (183) and 95.72% (179) (p<0.01). Moreover, significant differences were noted in albumin and prealbumin between the two groups after surgery (p<0.05), along with that of total protein content (p<0.001), especially in the software application group. Conclusion: The application of TPN management software in a cancer-specialised hospital not only standardised the doctor's TPN medical prescription, improved the efficiency and quality of prescription reviews by pharmacists, but also ensured the safe use of the medication and the effect of the treatment. No conflict of interest